The relationship between cerebrospinal fluid osteopontin level and central nervous system involvement in childhood acute leukemia - Incesoy-Özdemir, Sonay; Sahin, Gürses; Bozkurt, Ceyhun; Oren, Ayşe Ceyda; Balkaya, Eda; Ertem, Ulya (The Turkish Journal of Pediatrics, 2013)
The aim of this study was to evaluate the relationship between cerebrospinal fluid (CSF) osteopontin (OPN) levels and central nervous system (CNS) involvement in children with a diagnosis of acute leukemia. The study sample consisted of 62 patients who had been diagnosed with acute leukemia. The control group consisted of 16 patients that had presented and had no malignant disease, CNS infection or chronic disease. CSF OPN levels were studied with enzyme-linked immunosorbent assay (ELISA) method. The mean CSF OPN level was 32.76±49.22 ng/ml in the patients at the time of diagnosis and 14.93±6.84 ng/ml in the control group (p>0.05). The mean CSF OPN level was 27.68±32.73 ng/ml at the time of diagnosis in the group without CNS involvement and 53.48±89.21 ng/ml in the group with CNS involvement (p>0.05). However, the CSF OPN level at the time of CNS relapse in patients who developed CNS involvement during follow-up (127.4±52 ng/ml) was significantly higher than in the group without CNS involvement at diagnosis and follow-up (mean CSF OPN level: 27.68±32.73 ng/ml) (p